The Great Export Recovery in German manufacturing industries, 2009/2010 - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This paper uses comprehensive high-quality panel data from official statistics for exporting enterprises to investigate the micro-structure of the recent export recovery in 2010 in manufacturing industries in Germany after the great recession of 2008/2009. Almost all of the increase in exports was due to positive changes of exports in firms that continue to export (i.e. at the so-called intensive margin) while the increase of exports due to export starters (at the so-called extensive margin) was tiny. It is shown that Idiosyncratic shocks to very large firms played a decisive role in shaping the export recovery. These findings are remarkably symmetric to the results from an analysis of the great export collapse of 2008/09.
Keywords: F14; E32; 330; Exports; great export recovery; granular economy; Germany; Exportindustrie; Konjunktur; Wirtschaftskrise; Deutschland